COMPARATIVE ANALYSIS OF THE NATIONAL ACCOUNTS OF THE RUSSIAN FEDERATION AND JAPAN - George A. Ovchinnikov; Peter V. Akinin (Вестник Северо-Кавказского федерального университета, 2022)
The authors lead the national accounts of Russia and Japan. The article analyzes the main indicators, which are indicators of the state of the economies of. Produced comparison of Russia and Japan on the sus- tainability of the economies of the countries in the various shocks, primarily to the global financial crisis.